Of Darwin and Other Demons: the Evolutionary Turn in Aesthetics - Seghers, Eveline (Kultura-Społeczeństwo-Edukacja, 2015)
Evolutionary aesthetics attempts to explain the human ability to perceive objects, conspecif ics and the surrounding environment in an a es thetic manner - i.e. in an emotional and evaluative way resulting in a positive or negative appraisal - by referring to the evolutionary history of our functional, cognitive make-up. Research has mostly focussed on aesthetic considerat ions made during landscape assessment and on the role of aesthetic elements during mate choice. Criticism has been expressed repeatedly as to the naturalistic, presumed to be reductionist methods and outlook of an evolutionary approach to aesthetics. This paper briefly reviews the outline of evolutionary aesthetics research and discusses three such critiques - functionality in beauty judgement, reductionism, and the recognition of cultural and interindividual differences. It argues that philosophical aesthetics is not in danger of being unjustly reduced to a neurobiological explanation of aesthetic judgement and experience, and that evolutionary and traditional humanities approaches can be complementary in understanding our sense of beauty.